El resurgimiento de la xenofobia y la crisis del multiculturalismo. Una lectura desde el psicoanálisis - Espinoza Rivera, Jerry (2013)
This paper examines the problem of xenophobia based on the contributions to psychoanalytical theory made by Freud and Lacan. It proposes an interpretation of this phenomenon using the Freudian concept of “narcissism of small differences”, the Lacanian theory of the mirror stage and his explanation of the imaginary formation of the ego. Finally, it suggests that an alternative to confront this problem can be found in the political alternative of agonistic democracy made by Mouffe.